Radiation dose to the left anterior descending coronary artery during interstitial pulsed-dose-rate brachytherapy used as a boost in breast cancer patients undergoing organ-sparing treatment - Sinacki, Marcin; Serkies, Krystyna; Dziadziuszko, Rafał; Narkowicz, Magdalena; Kamińska, Joanna; Lipniewicz, Joanna (Journal of Contemporary Brachytherapy, 2017)
Purpose: To assess dose received by the left anterior descending (LAD) coronary artery during interstitial pulsed-dose-rate brachytherapy (PDR-BT) boost for left-sided breast cancer patients undergoing organ-sparing treatment. Material and methods : Thirty consecutive pT1-3N0-1M0 breast cancer patients boosted between 2014 and 2015 with 10 Gy/10 pulses/hour PDR-BT following a computed tomography (CT) simulation with the multi-catheter implant were included. The most common localization of primary tumor were upper quadrants. Patients were implanted with rigid tubes following breast conserving surgery and whole breast external beam irradiation (40 Gy/15 or 50 Gy/25 fractions). Computed tomography scans were retrospectively reviewed and LADs were contoured without and with margin of 5 mm (LAD 5mm ). Standard treatment plan encompassed tumor bed determined by the surgical clips with margin of 2 cm. Dosimetric parameters were extracted from the dose-volume histograms. Results : The mean D 90 and V 100 were 10.3 Gy (range: 6.6-13.3), and 42.0 cc (range: 15.3-109.3), respectively. The median dose non-uniformity ratio (DNR) was 0.50 (range: 0.27-0.82). The mean doses to LAD and LAD 5mm were 1.0 Gy and 0.96 Gy, and maximal doses were 1.57 Gy and 1.99 Gy, respectively. Dose to the 0.1 cc of the LAD and LAD 5mm were 1.42 Gy and 1.85 Gy (range: 0.01-4.98 Gy and 0.1-6.89 Gy), respectively. Conclusions : Interstitial multi-catheter PDR-BT used as a boost for left-sided breast cancer is generally associated with low dose to the LAD. However, higher dose in individual cases may require alternative approaches.